2011
DOI: 10.1080/08824096.2011.565278
|View full text |Cite
|
Sign up to set email alerts
|

Satire, Punch Lines, and the Nightly News: Untangling Media Effects on Political Participation

Abstract: Research often collapses programming like The Daily Show, The Colbert Report, The Late Show, and The Tonight Show into one category of programming. However, recent research suggests that both the content and effects of viewing these programs differ. This study separates satire or parody and traditional late-night comedy to examine effects of viewing on political participation. Results suggest that viewing satire or parody has positive and significant effects on political participation through the mediator of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 38 publications
1
101
0
1
Order By: Relevance
“…The current examination focuses on the criterion outcome variable of internal political efficacy, in part given extant research asserting the significant connections between exposure to various forms of comedy content (e.g., satirical programs like TDS; parody options like TCR or SNL; and online political humor from web sites like The Onion, JibJab, and Funny or Die) and internal political efficacy (Baumgartner & Morris, 2006;Becker, 2011;Hoffman & Young, 2011). Specifically, previous research by Baumgartner and Morris (2006) suggested that exposure to TDS is positively related to internal political efficacy, whereas recent work by Becker (2011) found that exposure to cable comedy content (e.g., TDS and TCR), online political humor, and cable news were positively related to efficacy.…”
Section: The Effects Of Politically Entertaining Media: Efficacy and mentioning
confidence: 99%
See 1 more Smart Citation
“…The current examination focuses on the criterion outcome variable of internal political efficacy, in part given extant research asserting the significant connections between exposure to various forms of comedy content (e.g., satirical programs like TDS; parody options like TCR or SNL; and online political humor from web sites like The Onion, JibJab, and Funny or Die) and internal political efficacy (Baumgartner & Morris, 2006;Becker, 2011;Hoffman & Young, 2011). Specifically, previous research by Baumgartner and Morris (2006) suggested that exposure to TDS is positively related to internal political efficacy, whereas recent work by Becker (2011) found that exposure to cable comedy content (e.g., TDS and TCR), online political humor, and cable news were positively related to efficacy.…”
Section: The Effects Of Politically Entertaining Media: Efficacy and mentioning
confidence: 99%
“…Each new election season brings a spate of Saturday Night Live (SNL) sketches, satirical critique from comedians like Jon Stewart of The Daily Show (TDS), doctored photographs and embellished headlines strewn across the pages of The Onion, and user-generated and professionally produced YouTube videos intended to entertain and, in some cases, persuade. Political communication researchers have taken a keen interest in studying this plethora of politically entertaining content with recent research efforts focusing on how political comedy is perceived and processed by viewers; the effects of exposure to political comedy content on key indicators of democratic engagement like participation and knowledge gain; the differential evaluation of varied humor types and programs; and, more recently, predicting consumption of political satire and a general affinity for politically humorous content (Becker, 2011(Becker, , 2012Becker, Xenos, & Waisanen, 2010;Hmielowski, Holbert, & Lee, 2011;Hoffman & Young, 2011;Xenos & Becker, 2009). To date, researchers have primarily focused on understanding the impact of exposure to satirical programs like TDS or The Colbert Report (TCR), the critical humor present in network late-night comedy monologues, and parody content airing on the weekly broadcasts of SNL.…”
Section: Introductionmentioning
confidence: 99%
“…Carnivalistic properties have scarcely been found in the mainstream media of Korea, which have long been criticized for their abuse of media power and indifference in citizens' authentic demands. It is very likely that the new journalism form created by the current-affairs podcasts provides a new momentum to the existing journalism routines and practices of Korea (Hoffman & Young, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Carnivalistic properties have scarcely been found in the mainstream media of Korea, which have long been criticized for their abuse of media power and indifference in citizens' authentic demands. It is very likely that the new journalism form created by the current-affairs podcasts provides a new momentum to the existing journalism routines and practices of Korea [47].…”
Section: Discussionmentioning
confidence: 99%